2013
DOI: 10.1111/bjd.12382
|View full text |Cite
|
Sign up to set email alerts
|

Atopic dermatitis complicated by eczema herpeticum is associated with HLA B7 and reduced interferon-γ-producing CD8+ T cells

Abstract: These data suggest that defects in viral-induced IFN-γ from CD8+ T cells contribute to the ADEH+ phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 11 publications
0
29
0
Order By: Relevance
“…However, the molecular mechanism underpinning the susceptibility to herpes virus infection remains poorly understood. Aberrations observed in eczema herpeticum patients point to the importance of impaired anti-viral immune response 10 , diminished activation of CD8+ cytotoxic T cells 11 , and production of indoleamine 2,3-dioxygenase by antigen presenting cells residing in the skin 12 . We and others have shown, that LCs play a central role in the regulation of CD8 T cell-mediated cytotoxic immunity through their unique ability to efficiently cross-present antigens and induce effective CD8 T cell responses 2, 3, 13 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the molecular mechanism underpinning the susceptibility to herpes virus infection remains poorly understood. Aberrations observed in eczema herpeticum patients point to the importance of impaired anti-viral immune response 10 , diminished activation of CD8+ cytotoxic T cells 11 , and production of indoleamine 2,3-dioxygenase by antigen presenting cells residing in the skin 12 . We and others have shown, that LCs play a central role in the regulation of CD8 T cell-mediated cytotoxic immunity through their unique ability to efficiently cross-present antigens and induce effective CD8 T cell responses 2, 3, 13 .…”
Section: Introductionmentioning
confidence: 99%
“…89,90 Our data show that petrolatum boosts the T H 1/IFN-g responses in patients with AD, potentially ameliorating a defective antiviral mechanism in patients who are prone to recurrent viral skin infections. Additionally, petrolatum occlusion resulted in reduced cellularity and strong induction of AMPs in AD skin, although to a lesser extent than in non-AD skin.…”
Section: Discussionmentioning
confidence: 76%
“…Recent studies have shown that the subset of patients with atopic dermatitis who are prone to eczema herpeticum (ADEH+) have a distinct phenotype; they have more severe atopic skin disease, are more likely to have a food allergy and asthma, and are more prone to cutaneous skin infections 2 7. Research into cell-mediated immunity defects in the ADEH+ group of patients has found an association with the human leucocyte antigen B7 allele and that expression of interferon (IFN)-γ was lower in CD8+ T cells and monocytes when exposed to HSV 8. An in vitro study has found that regulators of type I and type III IFNs, which are important in fighting HSV infections, are downregulated 9…”
Section: Discussionmentioning
confidence: 99%